Identidad y diferencia en The Cloning of Joanna May de Fay Weldon - Caporale Bizzini, Silvia (Miscelánea: A Journal of English and American Studies, 1995)
The aim of this paper is to carry out a reading of Fay Weldon's novel The Cloning of Joanna May. This work is the ironic answer Weldon gives to a culture that uses the negation of difference as a means to contain the feminine subject within the limits of the normative identity that the Cartesian ontology has assigned to women. In The Cloning of Joanna May, the discourse on gender is closely related to the discourse on the construction of identity. Weldon not only proposes a revision of the histories of women that belong to different social classes and educational backgrounds: she relates these histories to issues that explore the relation which exists between the feminine identity and social structures.